Chronic Urticaria: A Cutaneous Manifestation of Celiac Disease - Jessica Haussmann; Arni Sekar (Canadian Journal of Gastroenterology)
Celiac disease, or gluten-sensitive enteropathy, is an immune-mediated disease of the small bowel that results in malabsorption. It classically presents with gastrointestinal symptoms including chronic diarrhea, weight loss, abdominal bloating and anorexia. It is becoming more frequently identified in asymptomatic patients with a diagnosis of deficiencies related to malabsorption of iron, folic acid, vitamin B12 and vitamin D. It is increasingly identified as a cause for early or refractory osteoporosis. Occasionally, celiac disease presents with cutaneous manifestations alone. Dermatitis herpetiformis is a well-recognized cutaneous manifestation of celiac disease. Other cutaneous manifestations include alopecia, angular stomatitis and aphthous ulcerations. Described here is a case of a 24-year-old woman who presented with intermittent urticaria and gastrointestinal complaints. She was found to have celiac disease on small-bowel biopsy. Both her gastrointestinal symptoms and urticaria resolved when she was put on a gluten-free diet, suggesting that her urticaria was a cutaneous manifestation of celiac disease.